2016
DOI: 10.1177/2158244016635255
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information Seeking Pattern Among Undergraduates in a Nigerian University

Abstract: Based on a cross-sectional design, this study investigates online health seeking and its possible influence on decision making among 400 university undergraduates in Nigeria. From the results, it was found that daily Internet use was on the average (33.7%), and use was constrained by the poor power supply, the high cost of the Internet access, and poor delivery of services. Health information sought covers nutrition, fitness/exercise, HIV/AIDS, malaria, sore throat, mental health, menstrual pain, and sexual/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
2
44
0
1
Order By: Relevance
“…In another study at Tabriz University, participants approved the effects of their online health information seeking on the some health-related behaviors [45]. A study among the Nigerian students has found that only 50% of participants consulted with a physician about their health after searching online health information [38]. A study at 3 Ghanaian universities also reported that 72.4 percent of respondents used retrieved online information as a basis for lifestyles modifications and more than 73 percent of students stated that access to online health information improved or partially improved their health status, while 1.2 percent said that using Internet has no effect on their overall health [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study at Tabriz University, participants approved the effects of their online health information seeking on the some health-related behaviors [45]. A study among the Nigerian students has found that only 50% of participants consulted with a physician about their health after searching online health information [38]. A study at 3 Ghanaian universities also reported that 72.4 percent of respondents used retrieved online information as a basis for lifestyles modifications and more than 73 percent of students stated that access to online health information improved or partially improved their health status, while 1.2 percent said that using Internet has no effect on their overall health [32].…”
Section: Resultsmentioning
confidence: 99%
“…Supply side strategies: expanding internet access; providing high-quality, appropriate and understandable information; monitoring online health contents; engaging health professionals in producing evidence-based information; ensuring safety, paying attention to legal issues and focusing on adolescent health priorities are among the strategies of supply side [27,28,32,38].…”
Section: Resultsmentioning
confidence: 99%
“…• It is crucial to educate college students about searching and evaluating health information and thus improve their health literacy. Previous literature has shown that college students are not proficient in seeking health information (Banas, 2008;Stellefson et al, 2011;Obasola & Agunbiade, 2016). In this study, students also demonstrate that they can be biased by their own personal experiences or beliefs when assessing health information, raising concerns about potential pitfalls in students' health seeking journey due to such biases.…”
Section: Discussionmentioning
confidence: 67%
“…Ivanitskaya, Boyle and Casey (2006) used the Research Readiness Self-Assessment instrument to measure university student's health information literacy level, and found that many students were not able to conduct advanced information searches, judge the trustworthiness of health related websites and articles, and differentiate between various information sources. This finding was echoed by ensuing research on this topic (Banas, 2008;Stellefson et al, 2011;Obasola & Agunbiade, 2016). It was also worth noting that students tended to consider themselves as proficient in seeking health information though (Ivanitskaya, Boyl & Casey, 2006;Stellefson et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 98%
“…O conhecimento adequado sobre nutrição é importante para que cada pessoa possa tomar melhores decisões acerca da própria dieta 18 . Fontes comuns de informação sobre a nutrição incluem a internet, familiares, amigos, livros, a televisão e profissionais de saúde 19,20 .…”
Section: Desafios Para Manutenção Da Alimentação Saudávelunclassified